Archive [videorecording (DVD)] - Rothery, Gavin; James, Theo, 1984-; Martin, Stacy, 1991-; Mitra, Rhona, 1976-; Ferdinando, Peter (Vertical Entertainment, 2020)
In the near future, George Almore is working on a true human-equivalent AI. When his wife is tragically killed in a car accident, he becomes obsessed with the impossible: bringing her back to life. Her memories have been preserved thanks to the Archive, but only for so long. In a race against time, George must defy scientific and ethical boundaries to save the one he loves most.